Implementation of Remote Groundwater Filter With ESP32 based on Internet of Things - Supriyadi, Edy; Ariman, Ariman; Ilyas, Iriandi; Setiawan, Arso Bagus (International Journal of Advanced Multidisciplinary, 2025)
Conventional water filters available in the market cannot measure water quality, detect filter condition, automatically backwash when the filter is dirty and cannot be monitored anywhere. Therefore, by using ESP32, the filter condition can be determined and backwash if needed. From the existing problems, it is necessary to implement a control system and monitor the condition of the water filter, with the program features on the microcontroller and the web display used to control and monitor the tool, as well as internet of things-based testing and measurement of the tools made. From the research conducted, all sensors work well and the web display displays data in realtime so that it can support the performance of the tool to work as desired both automatically and manually.